Islamic art and the ethos of spirituality within a civilizational context - Grine, Fadila; Bensaid, Benaouda; Mohd Yusoff, M.Y. Zulkifli (Emerald Group Publishing Limited, 2013)
Islamic art is characterized by a deep-rooted vitality and distinct form of expression that arises from its intimate position with regard to Islamic civilization. While civilizational turning points and major occurrences have held deep ramiﬁcations for its growth and development, the most prominent catalysts of civilizational status are not only found in the realm of the political and economic, but rather within a deeper expanse of ideas, spirituality, and societal consciousness; of which Islamic art acts as a prime indicator. The paper aims to discuss these issues. Design/methodology/approach. This paper would seek to survey the depths inherent within Islamic spirituality’s relationship with Islamic art, and further isolate the reasons and source of their subsistence and continued prevalence. The paper further delves into the relationship shared by spirituality and art, and the inﬂuences they exert upon one another. Moreover, it attempts to delineate between the mundane and transcendental spheres of civilizational growth and development, while seeking to come to terms with the sustainability of Islamic art, and its position with respect to Islamic civilization. The paper concludes that Islamic art is sustained and deﬁned by means of a unique catalyzing ethos responsible for Islamic civilizational culture that is altogether distinct from the temporal mundane reality of socio-political conditions of civilization.